Health effects of cold water immersion and swimming and its influence on the human body - Lipińska, Justyna; Kowalczuk, Maria; Lipiński, Łukasz; Kopeć, Izabela; Margas, Mikołaj (Journal of Education, Health and Sport, 2024)
Introduction Immersing and swimming in cold water is an increasingly popular sport that has recently become a fashionable form of recreation in the winter months. People who regularly swim in cold water mention the many benefits associated with it. Aim of the study This review aims to present the current state of knowledge about immersion and swimming in cold water and to answer questions about the impact of this phenomenon on the human body and its health benefits. Materials and methods The PubMed database was used in this study.A literature review was conducted using the keywords “ice swimming,” “winter swimming,” “cold water swimming,” and “cold water immersion.” Results Much research has been done on the effects of cold water swimming, both positive and negative. Ice swimming affects many systems of our body, including the circulatory system, the immune system, and the endocrine system, and also affects metabolic and mental changes in our body, as shown in the work below. Summary A single immersion in cold water causes a stress reaction in the human body, while regular swimming in cold water causes the body to develop many positive physiological changes. Despite the benefits, it is still important to remember the risks involved, and more research should be done to minimize these dangers.